Human ecodynamics: A perspective for the study of long-term change in socioecological systems. (February 2019) - Fitzhugh, Ben; Butler, Virginia L.; Bovy, Kristine M.; Etnier, Michael A.
Abstract: Human ecodynamics (H.E.) refers to processes of stability, resilience, and change in socio-ecological relationships or systems. H.E. research involves interdisciplinary study of the human condition as it affects and is affected by the rest of the non-human world. In this paper, we review the intellectual history of the human ecodynamics concept over the past several decades, as it has emerged out of classical ecology, anthropology, behavioral ecology, resilience theory, historical ecology, and related fields, especially with respect to the study of long-term socioecological change. Those who study human ecodynamics reject the notion that humans should be considered external to the environments in which they live and have lived for millennia. Many are interested in the resilience and sustainability of past human-natural configurations, often striving to extract lessons from the past that can benefit society today. H.E. research, involving the study of paleoenvironments and archaeology, has taken shape around a series of methodological advances that facilitate the study of past chronology, paleoecology, paleodemography, mobility, trade, and social networks. It is only through integrated study of 'coupled human-natural systems'—'socio-ecosystems'—that we can hope to understand dynamic human-environmental interactions and begin to manage them for sustainable goals. Local and traditional or Indigenous knowledge provides another important influence to human ecodynamics research, and we explore how such knowledge can provide both expert witness into the operation of socioecological systems and insight into the human/cultural dimensions of those systems. Ultimately, we conclude that human ecodynamics is more encompassing than a number of related approaches and can provide a nexus for productive research. Through its interdisciplinary breadth, the framework unites scholarship that tends to be more isolated to address complex problems that are best tackled with diverse perspectives.